Two new species of Microcosmodes Strand (Coleoptera: Carabidae: Panagaenini) from Oman and Iran - Häckel, Martin; Azadbakhsh, Saeed (Zootaxa, 2016)
Two new species of the genus Microcosmodes Strand, M. arabicus from Oman and M. persicus from Iran, are described, compared with related taxa, and their affinities are discussed. The species are very similar and belong to the same species group.